Educación sensible como semiosis de mundo - López Delgado, Pedro Mario (Universidad Santiago de Cali, 2020)
This reflective is developed around Sensitive Education and its resonances with learning contexts where the development of imagination, sensory, perception, emotions, thoughts and feelings are favored towards to the strengthening of people ́s creating abilities. The core premises, around which experiences deployed are referenced in this text and confiigured in response to the intention of fostering a reflexive approach to the Orality ́s languages as a field of deep poiesics resonances, from which the emergency is possible for alternatives that privilege the configuration of a non-parameterized world sensitivity; validating the communicative-expressive power of Orality as a space of interaction, co-creation and reinvention capable to realize that we are a body in a sensitive relationship with other bodies.